Sedimentary Environment of a Modern Carbonate Platform of Karimunjawa Islands, Central Java - Solihuddin, Tubagus; Utami, Dwi Amanda; Salim, Hadiwijaya Lesmana; Prihantono, Joko (Indonesian Journal on Geoscience, 2019)
DOI: 10.17014/ijog.6.1.57-72Sitting in a biodiversity “hotspot” of the mid-Sunda Shelf region, Karimunjawa Islands have currently been the priority for marine biodiversity conservation. Knowledge of surface sediments on modern carbonate platform is one of essential information to support conservation policies, but such has received little attention from reef researchers. This study describes the sediment characteristics of the selected modern carbonate platforms of Karimunjawa Islands through integrated sediments and satellite data analysis. Textural group of sediments indicates that moderate to poorly sorted gravelly sands are dominant with no grading pattern concerning geomorphological and habitat succession from landward to seaward. Sediment compositions are predominantly bioclastic components, comprising coral and mollusks as the highest and the second highest estimated order of abundance. The reworked grains and rock fragments, although present, are not volumentary abundant. The carbonate sedimentary facies is primarily composed of mud-lean packstone with additional proportion of grainstone and packstone. There are only slight distinct sedimentological characteristics for all benthic habitats as shown by the principal component analysis revealing overlap relationship between sediment parameters and benthic habitats. The study provides the first characterization of sediments which operate on the modern carbonate platform of Karimunjawa Islands along with their controlling factors and specialized nature.